Pendampingan Literasi Dasar Tahap Pengembangan di SD Kristen YBPK Kota Malang - Eni Maharsi; Aris Siswanti; Melania Shinta Harendika (University of Merdeka Malang, 2021)
The implementation of Basic School Literacy Movement is supposed to be a shared responsibility, namely among parents, family, teachers, and the nation. But, notwithstanding it, this movement faces various obstacles in its implementation, including the students' reading and writing abilities, the parents’ economic background, and the competence of teachers as the central agents in the Basic Literacy Movement. These obstacles are being faced by YBPK Christian Elementary School Malang City. Thus, this community service programme aims at assisting and supporting the school in carrying out basic literacy movement in the development stage. The programme design includes two activity by considering teachers and student sides. The teachers were provided with training on how to teach basic literacy and with assistance in implementing the teaching method in development stage of literacy. The students were given activities designed to focus on achieving Story Discussion skills. Toward this end, teachers and students were equipped with Literacy Love Board Method as a tool to recognize and appreciate students’ active participation in the daily reading literacy. This Community Service Programme is expected to enhance basic literacy in the development stage towards the creation of a physical, social, affective, and academic literacy school environment.DOI: https://doi.org/10.26905/abdimas.v6i1.5007